Understanding More Than 50 Years of Mass Public Shootings as a Function of Routine Activities - Schildkraut, Jaclyn (Homicide studies, 2024)
Mass public shootings have drawn considerable attention from the public, policymakers, and researchers, yet despite what is known about these events, assessments to date have failed to consider their timing as a function of the locations where they occur. Using data on 401 U.S. mass public shootings occurring between 1966 and 2020, we examine these events’ temporal patterns. The findings suggest that the occurrence of mass public shootings may not be as random as once assumed but instead mirror the routine activities of the perpetrators, their victims, and the shootings’ locations. Considerations for prevention and response policies also are offered.